Optimalisasi Pendapatan Asli Daerah Melalui Program Daerah Agraria di Surakarta - Sava, Farrel Ridho Ian; Subekti, Rahayu; Raharjo, Purwono Sungkowo (Fakultas Hukum Universitas Primagraha, 2024)
With the Covid-19 pandemic that has hit all of Indonesia, it has caused losses that have had a huge impact on people's lives. This of course not only has an impact on the central government but also has an impact on regional governments because each region has its own responsibility to protect and serve the community. in the region, in this way the regional government also gets a very pronounced impact, especially in the Original Regional Income (PAD) sector. Original Regional Income itself is very important for regional governments because Original Regional Income itself is one of the sources of regional government financing and regional development, In ithe future, Regional Original Income will be used to finance expenditure from the regional government itself and for development costs for the region itself, for example the development of tourist areas, government programs that benefit the community and the regional government itself, and so on. In the explanation above, of course, in implementing this regional program, there are of course obstacles. With the obstacles that arise, they must be resolved and there must be a solution that might or could be implemented in other regions and be beneficial for other regions in terms of the Agrarian Regional Program.